Design of Hydrogel for the Drug Delivery of Less Permeable Ursolic Acid Isolated from Rhododendron arboreum Flower in Animal Skin Membrane - Joshi, Bigyan; Bhandari, Netra Lal; Shyaula, Sajan Lal; Budathoki, Uttam; Gyawali, Rajendra; Thapa, Panna (Journal of Nepal Chemical Society, 2024)
Ursolic acid (UA) is a pentacyclic triterpene that has antioxidant, anticancer, and anti-inflammatory properties. As it belongs to the biopharmaceutical classification system IV due to its poor water solubility and permeability restricts its use in clinical application. So, the research is focused on the development of hydrogel containing encapsulated liposomes of ursolic acid to increase its permeability. The ursolic acid liposomal gel was prepared with a 0.5%, 1%, and 1.5% mixture of carbopol 934P and HPMC K4M as gelling agents. The pH and spreadability of liposomal gel were found to be in the range of (6.93±0.035 to 7.12±0.03) and (15.41±0.36 to 24.47±0.90) g.cm/sec respectively. The drug content was found to be in (19.77±0.02 to 20.11±0.02)%. The study of drug release kinetics showed Higuchi release followed by a non-Fickian diffusion mechanism. The result of the permeation study by Franz diffusion cell showed 1.55 times higher compared to the plain gel at the 5th hour of the study with a flux value of 0.455(mg/cm2/hr). It resolved the fast and enhanced delivery of liposomal ursolic acid through the skin membrane.